Theoretical Comparative Syntax - Fukui, Naoki (Routledge Leading Linguists, 2006)
Collected for the first time in a single volume, these essays and articles by Naoki Fukui form an outline of some of the most significant and formative contributions to syntactic theory. Focusing particularly on the typological differences between Eng/type language and Japanese/type languages, Fukui examines the abstract parameters that both link and divide them. Linguistic universals are considered in the light of cross-linguistic variation and typological (parametric) differences are investigated from the viewpoint of universal principles. The book's main focus is the nature and structure of invariant principles and parameters (variables) and how they interact to give principled accounts to a variety of seemingly unrelated differences between Eng and Japanese. The contrasts between these two types of language is an ideal testing ground, since the languages are superficially different in virtually every aspect of their linguistic structures from word order and wh-movement, to grammatical agreement and case-marking systems, among many others. These articles constitute a considerable contribution to the development of the principles-and-parameters model in its exploration and refinement of theoretical concepts and fundamental principles of linguistic theory, leading to some of the basic insights that lie behind the minimalist program.